The Influence of Employee Engagement and Organizational Culture on Employee Performance at tabbleware Companies in Tangerang Regency. - Handayani, Fitria; Sukarya, Yaya; Agung Priyono, Agung Priyono (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2025)
This study aims to analyze the influence of employee engagement and organizational culture on employee performance at a tabbleware company in Tangerang Regency. Employee performance is an important factor in the company's progress, which is influenced by the emotional involvement of employees in their work and the organizational culture that applies in the company. This study uses a quantitative approach with a survey method. The population in this study were all employees of the printing company, with a sample of 30 people. Data were collected through distributing questionnaires that had been tested for validity and reliability. The results of the validity test showed that all items in the employee engagement, organizational culture and employee performance variables had values ??exceeding r table so that they were declared valid. Reliability tests with Cronbach's Alpha showed that all studies were reliable. Multiple linear regression analysis showed that employee engagement had a positive and significant effect on employee performance, as did organizational culture. The F test showed that simultaneously, employee engagement and organizational culture had a significant effect on employee performance with a significant value, and f count was greater than f table. This strengthens the suspicion of the study with the results of the study that employee engagement and organizational culture were influenced by employee performance, where the rest were not explained in this study, namely influenced by compensation and the work environment. Based on these findings, tabbleware companies are advised to improve employee engagement and organizational culture to maximize employee performance.